Awareness of Obstetricians/ Gynecologists Regarding the Role of Physiotherapy Services in Managing Obstetric Patients - Hina Munawar; Ayesha Tasadduq; Nosheen Zehra (ziauddin University, 2024)
Background: During the whole period of pregnancy women's body undergoes various physical and physiological changes. Due to the change during and after pregnancy common problems faced by the women's are low back pain, stress urinary incontinence, pelvic pain. Physiotherapy can help in this through postural reeducation, strengthening of pelvic floor muscles and through some modalities. Objective: To assess the awareness of obstetricians/ gynecologist regarding the role of physiotherapy in managing obstetric patients. Methods: A cross-sectional study was done among gynecologists and obstetricians selected from tertiary care hospitals of Karachi through non-probability convenient sampling, total sample size of the study was 300. Data was entered and analyzed by using SPSS version 17. Chi square test was used to find association for qualitative variables and p value <0.05 was considered as significant. Results: From the sample size (n=300) including gynecologists/obstetricians 123(41%) were from government hospitals and 177(59%) from private settings, 156(52%) had 3 to 5 years of experience while 144(48%) had more than 5 years of experience. Regarding referral during antenatal and postnatal period, it was found that 41(13.7%) participants advised most of the time, 203(67.7%) occasionally and 56(18.7%) never advised their patients. Out of total, 194(64.7%) had an awareness about pre-natal physiotherapy exercises sessions but only 56(18.7%) refer their patients for the antenatal classes (p-value 0.001). From total 204(68.0%) answered yes regarding the role of postnatal exercise sessions but out of them only 60(20.0%) refer for the post-natal physiotherapy sessions regularly and 74(24.7%) occasionally (p-value=0.218). Conclusion: Obstetrician/ Gynecologists had awareness about the role of physiotherapy in management of their obstetric patients but only a small portion of them concern and refer their patients for physiotherapy. Key Words: Awareness, Obstetricians/Gynecologists, physiotherapy, Obstetric patients